2004
DOI: 10.1074/jbc.m400371200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of the Herpes Simplex Virus Type I Origin-binding Protein Are Controlled by Precise Interactions with the Activated Form of the Origin of DNA Replication

Abstract: The herpes simplex virus, type I origin-binding protein, OBP, is a superfamily II DNA helicase encoded by the UL9 gene. OBP binds in a sequence-specific and cooperative way to the viral origin of replication oriS. OBP may unwind partially and introduce a hairpin into the double-stranded origin of replication. The formation of the novel conformation referred to as oriS* also requires the single-stranded DNA-binding protein, ICP8, and ATP hydrolysis. OBP forms a stable complex with oriS*. The hairpin in oriS* pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The hairpin is stably bound, in a sequence-specific manner, by the C-terminal domain of OBP, and the single-stranded AT-rich spacer is contacted by the N-terminal helicase domains (Fig. 2) (26). A dimer of OBP can simultaneously bind two double-stranded DNA ligands but only one copy of a box I/box III hairpin with a 10-nucleotide single-stranded tail (26).…”
Section: Activation Of Origins Of Dna Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The hairpin is stably bound, in a sequence-specific manner, by the C-terminal domain of OBP, and the single-stranded AT-rich spacer is contacted by the N-terminal helicase domains (Fig. 2) (26). A dimer of OBP can simultaneously bind two double-stranded DNA ligands but only one copy of a box I/box III hairpin with a 10-nucleotide single-stranded tail (26).…”
Section: Activation Of Origins Of Dna Replicationmentioning
confidence: 99%
“…A dimer of OBP can simultaneously bind two double-stranded DNA ligands but only one copy of a box I/box III hairpin with a 10-nucleotide single-stranded tail (26). It has been argued that this finding reflects a conformational change in OBP, from an origin-binding conformation to a helicase conformation, which can be facilitated by the interaction between ICP8 and the WPXXXGAXXFXXL motif found in the extreme C terminus of OBP (20,26). When ICP8 is in contact with ssDNA, this interaction can no longer be sustained (27).…”
Section: Activation Of Origins Of Dna Replicationmentioning
confidence: 99%
“…Recruitment of ICP8 is probably also important for recruiting the rest of the replication complex. Finally, we note that our work principally concerns the proteins bound to duplex Box I and pays scant attention to the rearrangement of oriS and the possible binding of UL9 to a DNA hairpin formed from Box I and Box III, which is reported (3,17) to form upon activation of the origin, oriS.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of ICP8, UL9 will open dsDNA containing Box I, leading to a conformational change in the origin, thus facilitating unwinding (14 -16). As stated above, the changes in DNA conformation in the complete oriS may be more complex (3). Recently, it has been suggested that single-stranded oriS folds into a unique and evolutionarily conserved conformation, oriS*, which is stably bound by UL9.…”
mentioning
confidence: 99%
“…Other viral mechanisms for initiation of DNA synthesis involve the creation of a site of initiation and are exemplified by adeno-associated virus (AAV), where the AAV Rep protein recognizes and nicks a stem-loop structure within the origin of replication (6). All of these proteins exhibit specific activity for nucleic acid binding to a sequence or structure within the lytic origin, and this activity consequently targets the protein to the site of DNA synthesis (20,21,24,35,40,42,45). The initiation of HCMV DNA replication appears to be more complex than that of other herpesviruses in that oriLyt spans nearly 3 kb and contains many cis-acting features such as transcription factor binding sites, RNA/DNA hybrid structures, and proposed stem-loop structures (2,25,32).…”
mentioning
confidence: 99%